IMPLEMENTATION OF LEARNING MANAGEMENT SYSTEM (LMS) IN PNS COMPETENCY DEVELOPMENT ACTIVITIES IN BPSDM GORONTALO PROVINCE - Laraga, Riwan (Journal of Research and Innovation In Open and Distance Learning, 2024)
Digital transformation in the bureaucratic environment is not something new, but it appears that it has not been implemented evenly and quickly, both in its implementation and in adapting to technology transfer by the bureaucracy and service users. Digital-based bureaucratic implementation is still dominant in financial matters. The end of 2019 was a momentum to accelerate the digital transformation of the bureaucracy, because the bureaucracy was faced with a situation where it was inevitable that they had to use digital services to avoid physical connections considering the corona virus or Covid-19 outbreak. No exception, civil servant competency development activities through training must be carried out with a new concept, namely digitally. Learning Management System (LMS) in training activities as a solution so that competency development can still be implemented. Of course, this must be adapted according to the demands of needs while still considering effectiveness and efficiency. The manifestation of the accelerated transformation of competency development through digital learning can be seen from various LMS implementation policies by the State Administration Institute of the Republic of Indonesia (LAN RI) as the supervisory agency. This scientific paper will analyze the application of LMS in the implementation of competency development through training attended by civil servants. Apart from that, it will also explain how it is implemented by elements of training organizers and managers as well as widyaiswara as facilitators to training participants. The approach in this research is descriptive qualitative which will interpret the phenomena found at the BPSDM research location in Gorontalo Province. Sampling was carried out by purposive sampling of Widyaiswara, Latsar participants, PKA participants, PKP participants, training managers and training organizers. A literature study was carried out to understand the concept of implementing an LMS based on existing regulations and to interpret studies in the literature related to digital transformation, especially LMS. The research results illustrate that LMS is very useful for developing employee competency, but its use is still deemed to be less effective due to the limitations of training participants, training organizers and managers as well as Widyaiswara in exploring the use of the LMS provided by LAN RI.